Struktur Kebahasaan Bahasa Indonesia sebagai Rujukan Penggunaan Bahasa (Fonologi) - Siti Ayudiah Alim; Rahma Ashari Hamzah; Siti Nuryati (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
A field of linguistics called phonology investigates the sound system of language, especially how sounds function to distinguish the meaning of words. The purpose of this study is to improve our understanding of the phoneme analysis of Indonesian. As the smallest units of sound, phonemes play an important role in distinguishing the meaning of words. The study of phonology includes the perception and production of sounds, their role in distinguishing meaning, and how sounds are used to create words and sentences. Phonology also investigates sound transformations such as assimilation, dissimilation, metathesis, and elision, which have an impact on the sound structure of language. Suprasegmental elements such as intonation, stress, and pauses are also discussed because they contribute to a clearer understanding of speech. In order to learn correct pronunciation and understand how sounds change as language develops, an understanding of phonology is essential.